The Role of Religion in Businesses from a Three-Dimensional Perspective - Entrepreneurship, Marketing and Organizational Management - Agheorghiesei, Daniela Tatiana (Journal for the study of religions and ideologies, 2016)
The teaching of religion in public schools - whether the subject should or should not be included in the school curricula, what the content structure should be and which approach the teacher should adopt - led to various ethical dilemmas and conflicts in many regions of the world. Our article aims at reviewing, from the perspectives of numerous authors, the different topics as well as the ways in which aspects related to the impact of religious teaching and to specific approaches could be taught to economics students in a democratic society. At the same time, we underline different dilemmas and preoccupations resulting from religious values in the organizational management and in marketing, but also the synergies that could be capitalized from this standpoint, in order to obtain a competitive advantage in a context where diversity (based on differences and similarities), and religious diversity in particular, is a reality that gets more and more obvious, while a good capitalization of it can bring forth loyalty in organizations and competitive advantages on the market.